Structural breaks and time-series analysis of Brazilian beef exports from january 2013 to december 2022 - Santos, Victor Lara (2024)
The following thesis aims to look for and analyze any unexpected changes in the Brazilian beef exports time-series and quantify the impact that certain events and variables had on it during the period of January 2013 to December 2022. The Bai & Perron (2003) structuralbreak model was used to check for unusual changes in the time-series; the Prais–Winsten (1954) estimation was used for a regression of the beef export volume time-series, with domestic and export prices of beef, chicken, and pork, income, exchange rate and time as the independent variables. This study will have a higher emphasis on describing the events that occurred within each Break that may have affected the international demand for Brazilian Beef. Comparisons with prior and similar research, such as the study done by Melz et al (2014) will be made in order to better contextualize and see the evolution of the Brazilian beef exports. It was found that the Brazilian Beef demand has constantly been achieving new record highs. It was also discovered that there was only one structural break in the period studied, with said break pertaining to the 2018 Brazilian truck drivers’ strike, which almost paralyzed the exports for its duration. Furthermore, it was discovered that the pandemic and Ukraine-Russia war did not negatively affect Brazilian Beef exports, and that the events that most impacted the export volume of Brazilian beef, besides the truck drivers’ strike, were exogenous events such as a prolonged Chinese embargo on Brazilian Beef, and widespread rumors and repercussions of the operation “Carne Fraca” (Weak Meat).